(untitled) (Prostor, 2024)
This study explores the historical development of military sites and their impact on land use in the European context. Reflecting broader social, political, and technological changes, the impact of military sites on urban and rural areas has undergone a notable transformation. By employing qualitative research methods, this study investigates demilitarisation challenges, transformations, and the integration of military sites into urban environments. It reveals societal perceptions, regulatory complexities, and spatial dynamics, thereby illuminating the potential of repurposing military sites for sustainable urban development. It uncovers the interplay between the military and civilian spheres through nuanced analysis, offering valuable insights into modern city development strategies. As this research unveils historical dynamics, it also provides crucial knowledge that can be employed in planning the future development of cities, considering the evolving relationship between military and urban spaces.